Identification of elk preferences for different diet supplements. (24th February 2016) - Braithwaite, Hope; Bateman, Timothy M.; Veblen, Kari E.; Thacker, Eric; Villalba, Juan J.
ABSTRACT: Although diet supplementation is a well‐established tool for managing livestock distributions and improving vegetation, the principle is less commonly applied to wild ungulates. One reason for this is that it is not known whether wildlife species, such as elk ( Cervus elaphus ), will habituate to novel supplements and feeders in the landscape. We, therefore, performed a pilot study during winters of 2013 and 2014 to test Rocky Mountain elk ( C. e. nelsoni ) preferences for 4 diet supplements—2 high in energy (beet pulp and molasses) and 2 high in protein (soybean meal and canola meal)—at a feeding ground in northern Utah, USA. We also tested elk preference for 2 types of feeders that differed in shape, size, and color. We measured the amounts of supplement consumed by elk and used observational techniques (scan sampling) to determine supplement and feeder preference. The weights of refused supplements showed that elk discriminated among supplements, showing greater preferences for high‐energy supplements during periods of low ambient temperatures ( P  < 0.05). Observational techniques revealed that elk preferred red, short, and wide feeders ( P  < 0.05). Our results illustrate that elk discriminate among diet supplements and feeder types, suggesting that diet supplementation may be a viable tool to relocate elk away from overused areas. © 2016 The Wildlife Society.